2003
DOI: 10.3354/cr024215
|View full text |Cite
|
Sign up to set email alerts
|

A statistical comparison of the stochastic weather generators WGEN and SIMMETEO

Abstract: Weather generators are frequently used to provide weather data when the length of historical weather data is inadequate or when future data are required. The main objective of this study was to evaluate the weather generators WGEN and SIMMETEO as implemented in the Decision Support System for Agrotechnology Transfer (DSSAT) for 5 Iranian locations with contrasting climates. The algorithms for generating weather data are the same in both programs, but they differ with respect to the methods used for parameter e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
32
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 37 publications
0
32
0
Order By: Relevance
“…The percentage significant differences (t * and F *) between observed and generated weather data when the length of input data is equal to the entire length of observed data (30 yr here; D 30 in Table 2) indicates the adequacy and validity of the generators. Details on the performance of the generators for the selected locations of this study can be found in Soltani & Hoogenboom (2003).The response of absolute difference between observed and generated weather variables (expressed in their physical unit) to the length of input data was similar to those of t* (Table 2). We prefer to use t*, because it is impossible to apply the segmented model (Eq.…”
mentioning
confidence: 72%
See 4 more Smart Citations
“…The percentage significant differences (t * and F *) between observed and generated weather data when the length of input data is equal to the entire length of observed data (30 yr here; D 30 in Table 2) indicates the adequacy and validity of the generators. Details on the performance of the generators for the selected locations of this study can be found in Soltani & Hoogenboom (2003).The response of absolute difference between observed and generated weather variables (expressed in their physical unit) to the length of input data was similar to those of t* (Table 2). We prefer to use t*, because it is impossible to apply the segmented model (Eq.…”
mentioning
confidence: 72%
“…Daily values are computed internally, using linear interpolation. More details can be found in Richardson (1981), Richardson & Wright (1984), Semenov et al (1998), and Soltani & Hoogenboom (2003).The SIMMETEO generator of WeatherMan is embodied in the WGEN generator, but it uses different input data compared to WGEN. The modified SIMME-TEO model uses monthly climatic means of the number of wet days, precipitation, solar radiation, and maximum temperature and minimum temperature as well as regression equations to compute conditional means, standard deviations and precipitation parameters (Geng et al 1986, 1988, Pickering et al 1994.…”
mentioning
confidence: 99%
See 3 more Smart Citations